Diagnosing mitochondrial DNA diversity: applications of a sentinel gene approach - Clare, E.L.; Hebert, P.D.N.; Wilson, J.J.; von Konigslow, T.E.; Kerr, K.C.R. (2008)
Mitochondrial genomes show wide variation in their GC content. This study examines the correlations between mitochondrial genome-wide shifts in this feature and a fragment of the cytochrome c oxidase subunit I (COI) gene in animals, plants, and fungi. Because this approach utilizes COI as a sentinel, analyzing sequences from repositories such as GenBank and the Barcode of Life Data System (BOLD) can provide rapid insights into nucleotide usage. With this approach we probe nucleotide composition in a variety of taxonomic groups and establish the degree to which mitochondrial GC content varies among them. We then focus on two groups in particular, the classes Insecta and Aves, which possess the highest and lowest GC content, respectively. We establish that the sentinel approach provides strong indicators of mitochondrial GC content within divergent phyla (R values = 0.86-0.95, p < 0.001, in test cases) and provide evidence that selective pressures acting on GC content extend to noncoding regions of the plant and fungal mitochondrial genomes. We demonstrate that there is considerable variation in GC content of the mitochondrial genome within phyla and at each taxonomic level, leading to a substantial overlap zone in GC content between chordates and invertebrates. Our results provide a novel insight into the mitochondrial genome composition of animals, plants, and fungi and advocate this sentinel technique for the detection of rapid alterations in nucleotide usage as a measure of mitochondrial genome biodiversity.